Perceived social norms and agripreneurial intention among youths in eastern DRC - Ephrem, A.N.; Dontsop Nguezet, Paul M.; Murimbika, M.; Bamba, Z.; Manyong, Victor (MDPI, 2021)
The Democratic Republic of the Congo (DRC) is a country with a high agricultural productivity potential; however, the agribusiness sector remains unattractive to youths. This study examined the extent to which perceived social norms and psychological capital affect youths’ intentions to pursue agribusiness opportunities in the Eastern DRC. Data was collected on a sample of 600 youths. We applied Partial Least Squares Structural Equation Modelling (PLS−SEM) in order to examine the relationship between the variables. The findings indicated that most of the youths did not select agribusiness as their top career choice. The intention to engage in agribusiness activities was significantly higher among the youths who perceived that agribusiness was socially valued and supported. Psychological capital significantly and positively affects youths’ agripreneurial intention. The findings contribute to the underlying Theory of Planned Behavior by supporting a positive mediation role of psychological capital—and the moderating roles of educational level, gender, access to land, and location—on the relationship between perceived social norms and agripreneurial intention. The paper concludes that the provision of funds is not enough to promote youth agripreneurship in an environment in which agricultural-related social norms, youths’ psychological capital, gender, access to land, educational level, and location (rural versus urban) are not thoroughly considered.